Optimal Fixed Bed Reactor Network Configuration for the Efficient Recycling of CO2 into Methanol - Ali Elkamel; Ali Lohi; Chris Marton; Gholam Reza Zahedi (Energies, 2009)
An optimal design strategy of a network of fixed bed reactors for Methanol Production (MP) is proposed in this study. Both methanol production and profit spanning a production period of eight years have been set as objective functions to find the optimal production network. The conservation of mass and energy laws on a heterogeneous model of a single industrial methanol reactor was first developed. The model was solved numerically and was validated with industrial plant data. Different reactor network arrangements were then simulated in order to find an optimal superstructure. It was found that a structure of four reactors (two in series in parallel with another two in series) provide maximum production rate. The application of the more realistic objective function of profit showed that a configuration of two parallel reactors is the best configuration. This optimal structure produces 92 tons/day more methanol than a single reactor.